Hubungan Motivasi Guru Dengan Minat Baca Siswa Kelas VII Di SMP Negeri 12 Kota Sukabumi - Nuke Febriana; Tanti Agustiani; Fauziah Suparman (FKIP Universitas Muhammadiyah Sukabumi, 2019)
This study aims to measure the relationship between teacher motivation and students' reading interest in SMPN 12 Kota Sukabumi. The method used in this study is a quantitative method. The subjects of this study were 30 grade VII. Sampling in this study uses purposive sampling technique. Data collection techniques are carried out by observation, interview and questionnaire techniques. The data obtained is then processed. The result shows that there is a relationship between the motivation of the teacher and the reading interest of students in SMPN 12 Kota Sukabumi with a magnitude of 76%, this is evidenced by obtaining a correlation number of 0, 97 and the t test value obtained that t count> 21.11> 2.05, with a significant level of 0.05. In addition, because in this study obtained the results of tcount greater than t table, then the alternative hypothesis (Ha) submitted is accepted and Ho is rejected. So that from this whole study it can be concluded that there is a significant relationship between the motivation of the teacher and reading interest of the seventh grade students at SMPN 12 Kota Sukabumi.